2013
DOI: 10.3758/s13415-013-0197-z
|View full text |Cite
|
Sign up to set email alerts
|

I don’t feel your pain (as much): The desensitizing effect of mind wandering on the perception of others’ discomfort

Abstract: Mind wandering reduces both the sensory and cognitive processing of affectively neutral stimuli, but whether it also modulates the processing of affectively salient stimuli remains unclear. In particular, we examined whether mind wandering attenuates one's sensitivity to observing mild pain in others. In the first experiment, we recorded event-related potentials (ERPs) as participants viewed images of hands in either painful or neutral situations, while being prompted at random intervals to report whether thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 47 publications
5
31
0
1
Order By: Relevance
“…Likewise, our second experiment showed a corresponding behavioral effect, that is, a reduction of painfulness ratings of painful stimuli during mind wandering episodes (Kam et al, 2013b). Together, our findings suggest that mind wandering reduces our cognitive evaluation of external inputs even for affectively salient stimuli.…”
Section: Which Neurocognitive Functions Are Attenuated During the Decmentioning
confidence: 64%
“…Likewise, our second experiment showed a corresponding behavioral effect, that is, a reduction of painfulness ratings of painful stimuli during mind wandering episodes (Kam et al, 2013b). Together, our findings suggest that mind wandering reduces our cognitive evaluation of external inputs even for affectively salient stimuli.…”
Section: Which Neurocognitive Functions Are Attenuated During the Decmentioning
confidence: 64%
“…The absence of attentional state modulations in the behavioral measure highlights the importance and utility of ERP measures in examining the underlying neural mechanism that may not manifest as differences in manual reaction times. In addition, other EPR studies have that mind wandering periods are associated with disruptions in a range of cognitive responses, including stimulus evaluation and categorization (Barron, Riby, Greer, & Smallwood, 2011;O'Connell et al, 2009;Smallwood, Beach, Schooler, & Handy, 2008), affective processing (Kam, Xu, & Handy, 2014), and performance monitoring (Kam, Dao, Stanciulescu, Tildesley, & Handy, 2013). Of relevance, given that visual stimuli used in these previous studies have been presented along the midline of the visual field (e.g., Barron et al, 2011;Kam et al, 2011;Smallwood et al, 2008), to what extent would we observe a similar attenuation of sensory gain to task-irrelevant visual stimuli across both hemifields?…”
Section: Introductionmentioning
confidence: 98%
“…Since the publication of this review, Mrazek, Phillips, et al (2013) have similarly reported impaired reading comprehension associated with prompt-assessed mind-wandering. A number of further studies have found additional costs: attentional lapses associated with impaired performance on the Stroop task (Unsworth & McMillan, 2014), a significant relationship between mind-wandering proclivity and frequency of falls in older adults, presumably at least partly because of inattention to external stimuli (Nagamatsu et al, 2013), particularly in the left visual field (Kam, Nagamatsu, & Handy, 2014), and reduced empathic responses to others' physical discomfort, as assessed by participants' ratings and electrophysiologically with event-related potentials (Kam, Xu, & Handy, 2014). By contrast, when leaving aside its perseverative, ruminative forms, mindwandering appears unrelated to most measures of health Ottaviani, Shapiro, & Couyoumdjian, 2013).…”
Section: Costs Of Spontaneous Thoughtsmentioning
confidence: 99%